Reorientasi Pemidanaan Berbasis Pemulihan Pada Kejahatan Ekonomi - Ahmad Hiddin Susilo; Sri Rahayu Jamria; Shinta Ayu Purnamawati (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This article criticizes the dominance of custodial sentences in economic crime cases and proposes a recovery-based sentencing orientation as a measure of legal effectiveness. The study aims to construct recovery-oriented punishment through the objectives of sentencing theory of Barda Nawawi Arief and the legal effectiveness theory of Soerjono Soekanto, and to analyze why judges have not prioritized asset recovery in judicial practice. Using normative legal research with statutory and conceptual approaches, this study examines legislation, legal doctrines, and court decisions related to corruption, money laundering, and other economic crimes. The findings reveal that Indonesian law has provided adequate legal instruments for asset recovery through additional penalties, yet judges tend to treat them as complementary rather than primary considerations. This gap is influenced by sentencing orientation, limited understanding of additional penalties, technical obstacles in asset tracing, weak inter-agency coordination, and entrenched legal culture. The article argues that the effectiveness of punishment in economic crimes must be measured by the extent to which losses are restored, not by the length of imprisonment.